Green Entrepreneurship in Afghanistan: Prospects and Challenges - Mohsen, Ahsanullah (The Asian Journal of Technology Management (AJTM), 2018)
Abstract. Green entrepreneurship has a vital role in todayâ€™s world wherein several businesses are considering profit maximization and ignoring the environmental concerns to some extent. The prime purpose of this paper is to analyze and recognize the impending challenges and opportunities faced by entrepreneurs in Afghanistan. Furthermore, it provides suggestions on how to benefit from green entrepreneurship in order to avoid environmental degradation. This research is exploratory; nevertheless, it utilizes both primary and secondary data. The study uses factor analysis and correlation coefficient to analyze the data. The variables include motivational factors and those of barriers to green entrepreneurship in Afghanistan. The primary data is gathered from 100 business management students through a well-designed questionnaire. This paper is expedient to understand the motivational factors, which will create a platform for entrepreneurs to develop their strategies accordingly. The study also encompasses the key drivers for green entrepreneurship in Afghanistan. The findings show that growing awareness and demand for organic products amongst consumers, providing a sustainable solution to ecological dangers and prevention of further degradation, and social responsibility are the motivational factor for green entrepreneurship in Afghanistan. Based on the results of this study, the government needs to increase the awareness among the people and support the entrepreneurs who start a green business in Afghanistan.Keywords:Â  Entrepreneurship, environmental degradation, green entrepreneurship, green technology, green productÂ